2020
DOI: 10.21315/tlsr2020.31.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ectoparasitism on Small Ruminants in Kelantan, Malaysia

Abstract: Highlights• 60% of the sampled animals were infested with at least one species of the ectoparasites.• Lice and ticks were the most prevalent ectoparasites on small ruminant, which were 43.64% and 22.98% respectively.• The prevalence of ectoparasites on small ruminant is significantly higher at inland region.Abstract: Kelantan is a chiefly agrarian state with abundant small-holder ruminant farms in the East Coast economic Region of Malaysia. Ectoparasitism affects small ruminant production in Malaysia. It often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…We also reported that overall, Kelantan has the highest number of Malin sheep. This finding is in agreement with the report of [34], which described Kelantan as an agrarian state in which almost all herders have small livestock farms that contribute to economic growth within the east coast region of Peninsular Malaysia.…”
Section: E P T E Dsupporting
confidence: 93%
“…We also reported that overall, Kelantan has the highest number of Malin sheep. This finding is in agreement with the report of [34], which described Kelantan as an agrarian state in which almost all herders have small livestock farms that contribute to economic growth within the east coast region of Peninsular Malaysia.…”
Section: E P T E Dsupporting
confidence: 93%
“…This prevalence is higher than in Nganjuk, East Java [43] and Deli Serdang, North Sumatera [44], according to the only other related investigations reported in Indonesia to date. Given the infestation prevalence exceeding 90%, our result is higher compared to the prevalence of ectoparasite infestations observed in studies conducted in other countries and continents, i.e., in Malaysia [25], Pakistan [45], India [46], Iran [47], Nigeria [48], Ethiopia [49,50], Africa [51], the UK [52], Brazil [53], and Iraq [54].…”
Section: Discussioncontrasting
confidence: 56%
“…B. caprae is known as a chewing lice, while L. africanus is known as a blood-sucking lice [55]. Infestations of B. caprae and L. africanus have been reported at various rates in Indonesia [43], Malaysia [25], India [56], Egypt [57], Libya [58], and Brazil [59]. Lice having the highest prevalence among the ectoparasite types may indicate that they are easily transmitted within populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One group of obligate parasites commonly found on pets is lice, wingless insects that feed on their hosts by ingesting blood, feathers, mucus or skin debris (Durden, 2019). Previous studies on lice from Malaysia were mostly focused on companion animals, livestock and small mammals (Johnson, 1964;Mustaffa-Babjee, 1969;Norhidayu et al, 2012;Syamsul et al, 2020), but less is known on lice parasitising exotic pets. In this paper, we report two new records of chewing lice from avian pets in Peninsular Malaysia: Colpocephalum apivorus Tendeiro, 1958 from an Oriental honey buzzard [Pernis ptilorhynchus (Temminck, 1821)], and Myrsidea splendenticola Klockenhoff, 1973 from an albino house crow (Corvus splendens Vieillot, 1817).…”
Section: Introductionmentioning
confidence: 99%